Does Migraine Increase the Risk of Glaucoma?: A Population-Based Cohort Study. Issue 19 (May 2016) - Chen, Hsin-Yi; Lin, Cheng-Li; Kao, Chia-Hung
Abstract : Abstract: This study investigated whether migraine influences the risk of primary open-angle glaucoma (POAG) and primary angle-closure glaucoma (PACG) in Taiwan. We retrieved the data analyzed in this study from the National Health Insurance Research Database in Taiwan. We included 17, 606 newly diagnosed migraine patients without preexisting glaucoma and randomly selected and matched 70, 423 subjects without migraine as the comparison cohort. The same exclusion criteria were also applied to comparison subjects. Multivariate Cox proportion-hazards regression model was used to assess the effects of migraines on the risk of glaucoma after adjusting for demographic characteristics and comorbidities. The cumulative incidence of POAG was higher in the migraine cohort than that in the comparison cohort (log-rank P = 0.04). The overall incidence of POAG (per 10, 000 person-years) was 9.62 and 7.69, respectively, for migraine cohort and nonmigraine cohort (crude hazard ratio [HR] = 1.24, 95% confidence interval [CI] = 1.01–1.54). After adjusting the covariates, the risk of POAG was not significantly higher in the migraine cohort than in the comparison cohort (adjusted HR [aHR] = 1.15, 95% CI = 0.93–1.42). The cumulative incidence of PACG did not differ between the migraine cohort and the comparison cohort (log-rank test P = 0.53). The overall incidence of PACG was not significantly higher in the migraine cohort than that in the comparison cohort (7.42 vs 6.84 per 10, 000 person-years), with an aHR of 1.04 (95% CI = 0.82–1.32). This study shows that migraines are not associated with a higher risk either in POAG or in PACG.